Diseño de un entrenador de acondicionamiento de aire, automatizado, con una cámara con condiciones térmicas controladas (2019)
The present project is made up of five chapters, where the first one describes the generalities and concepts necessary in the course and development of the project. The second chapter refers to the trainer's design, parameters were implemented, a subdivision of the trainer was made into a structural system, humidifier and heater system, air conditioning system and instrumental and control system, afterwards the analysis was performed of alternatives for each system and selection of each alternative was given, with the aforementioned already proceeded to perform the calculation of the thermal load and the calculation of equipment, pipes, ducts and the structural system. The third chapter describes the instrumentation process and the control system established, together with the examples of each process that can be carried out in the trainer. The fourth chapter contains the trainer's installation guide, which describes step by step how the assembly of the equipment and the tools necessary to carry it out must be carried out. The fifth and final chapter contains the environmental analysis which analyzes the critical factors of the coach for the environment and the importance they have, also includes the description of the costs to carry out the implementation of the coach, such as equipment costs, costs of manufacturing and engineering costs. then the conclusions and recommendations of the project were made and finally there will be the annexes where the technical files and team catalogs will be along with the design plans of the trainer.